Planet and People Representations in PT Unilever Indonesia's Sustainability Report: A Semiotic Analysis - Nurhikmah Dewi Anugrah; Aunneke J Paembonan; Zuhalwah Yuliah Ilham; Darwis Said; Nadhirah Nagu (Manunggal Halim Jaya, 2027)
This study examines how the Planet and People dimensions are represented in PT Unilever Indonesia Tbk's 2025 Sustainability Report through Roland Barthes's semiotic perspective and explores their implications for green accounting practices. An interpretive qualitative approach was employed using document analysis and multimodal semiotics. The study analysed verbal, visual, and numerical signs within the sustainability report through the levels of denotation, connotation, and myth, supported by legitimacy theory, impression management, and decoupling. The findings indicate that the report constructs the company's environmental and social identity through integrated textual, visual, and numerical representations that reinforce its sustainability commitments and organisational legitimacy. However, the analysis also reveals asymmetries between the prominence of sustainability achievements and the disclosure of reporting limitations, creating a potential risk of semiotic greenwashing through selective representation rather than explicit misinformation. This study contributes to the accounting literature by demonstrating how semiotic analysis extends conventional assessments of sustainability reporting beyond disclosure content to examine how corporate legitimacy is constructed through representational practices. The findings also provide practical insights for improving the transparency, balance, and accountability of sustainability reporting and green accounting practices.